Assessing Patient Safety Culture in the Hospital: a Pilot Study Using a Modified Manchester Patient Safety Framework (MaPSaF) - Arum Astika Sari (Universitas Muhammadiyah Yogyakarta, 2017)
The aim of this study was to modify and determine the dimensions and themes of the patient safety culture tool by MaPSaF. This study was a qualitative design with study literature approach. The result of this study was MaPSaF composed of 10 dimensions of patient safety culture with 24 aspects which contain the statements in each theme. The dimensions are the commitment to overall continuous improvement, priority given to safety, system errors and individual responsibility, recording incidents and best practice, evaluating incidents and best practice, learning and affecting change, communication about safety issues, personnel management and safety issues, staff education and training, and teamwork. The aspects are committed to improvement, audit, policies, priority of patient safety, risk management system, implementation of patient safety, the cause of the incident, patient safety culture, reporting feeling and system, data analysis, the focus and result of investigation, incidents learning, the people in deciding of change, communication about patient safety between staff, patient or both, share the information, supporting the staff, training needs and purposes, team structure, the flow of information and sharing.